Provisioning System for Application Virtualization Environments - Buyuktanir, Tolga; Tuzun, Hakan; Aktas, Mehmet S. (IEEE, 2018)
Monitoring application resource dynamically in application virtualization environments and in case of any occurcncc of pre-determined rules, updating resources allocated to virtualization environment have become important requirement today. In this study, a resource monitoring and management software architecture for application virtualization environments has been designed and implemented as a prototype. Performance evaluation of implemented prototype has been carried out and all the results were observed to be succesful.
Keywords: application virtualizathm environments; docker container; provisioning; real-thne event anaylysis; Computer Science; Engineering